2003
DOI: 10.1029/2002gl016342
|View full text |Cite
|
Sign up to set email alerts
|

A sub‐tropical cirrus clouds climatology from Reunion Island (21°S, 55°E) lidar data set

Abstract: The aim of this work is to document cirrus characteristics using ground‐based measurements. A climatology of sub‐tropical cirrus clouds is presented from the analysis of the Rayleigh‐Mie lidar data collected at the “Observatoire de Physique de l'Atmosphere de la Reunion” (OPAR) over the period 1996–2001. The lidar laser operates at 532 nm. This climatology is based on the analysis of upward laser beam over 533 nights corresponding to 1643 hours of lidar probing. In this sub‐tropical zone, two main seasons prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 18 publications
2
25
0
1
Order By: Relevance
“…5520 E. Giannakaki et al: Characteristics of cirrus clouds over a lidar station Comstock and Ackerman (2002) have studied the optical and geometrical properties of tropical cirrus clouds and found that high clouds occur on average 44% of the time. Sub-tropical cirrus clouds are present more frequently at austral summer than the austral winter as Cadet et al (2003) have shown. The same study showed that 65% of the total cirrus observations are characterized as sub-visual, with an optical thickness of less than 0.03.…”
Section: Introductionmentioning
confidence: 66%
“…5520 E. Giannakaki et al: Characteristics of cirrus clouds over a lidar station Comstock and Ackerman (2002) have studied the optical and geometrical properties of tropical cirrus clouds and found that high clouds occur on average 44% of the time. Sub-tropical cirrus clouds are present more frequently at austral summer than the austral winter as Cadet et al (2003) have shown. The same study showed that 65% of the total cirrus observations are characterized as sub-visual, with an optical thickness of less than 0.03.…”
Section: Introductionmentioning
confidence: 66%
“…It is presumably the ambiguity in classifying a "warm" ice-phase cloud genus, combined with potential questions regarding the representativeness of a single study conducted at a single midlatitude site, which has precluded the adoption of the SC2001 threshold universally within the community with respect to autonomous lidar measurements (though some have applied it; e.g., Cadet et al, 2003). SC2001 acknowledge the latter point, declaring that "cirrus clouds are the product of weather processes such that their occurrence and macrophysical properties will vary significantly over the globe."…”
mentioning
confidence: 99%
“…On average this is equivalent to approximately 30 temperature profiles per month. Réunion and Mauna Loa temperature lidar profiles have been widely used in different research projects (Leblanc et al, 1998(Leblanc et al, , 1999Morel et al, 2002;Cadet et al, 2003;Bencherif et al, 2007;Dou et al, 2009;Sivakumar et al, 2011;.…”
mentioning
confidence: 99%